Mediatin in family business: finding a solution in family and commercial issues - Yuriichuk, Illia; Moisei, Heorhii (Університет «КРОК», 2021)
This article is about the aspects of mediation in family business disputes. Nowadays, all developed countries of the world are considered the recognition mediation as one of the most efficient methods to resolve a dispute. A mediator is a profes- sional who acts as a third party to resolve a dispute and helps opponents to communicate with one another, to guide the parties in their finding a solution that satisfies the interests and needs of both parties. In the article we discover a correlation between a family and business interests, analyze the meaning of the “family business conflict” concept, and discover a detailed and structured proce- dure of mediation in family business disputes. Moreover, it was compared the basic pros and cons of the family business mediation, which helps us to find out the strong and weak sides of such brand new type of mediation.
Keywords: mediation; family business; family and commercial issues; conflict; family business conflict; mediation process